Exploring the Current Status and Future Potential of Robot, Artificial Intelligence, and Service Automation in the Indonesian Tourism Industry - Agung Yoga Asmoro; Gareth Butler; Gerti Szili (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2023)
This paper examines the current state and potential future applications of robots, artificial intelligence, and service automation (RAISA) in the hospitality, travel, and tourism industry, with a focus on Indonesia. The study utilizes a comprehensive review of literature and empirical data, including case studies, industry reports, and scholarly articles, to gather relevant information. The findings reveal that while the implementation of RAISA in the Indonesian tourism industry is still in its introductory stage, advancements in RAISA technology and decreasing costs make it increasingly viable for substituting human labor in repetitive and high-risk tasks. However, it is important to consider that not all service processes are suitable for automation or delegation to robots. The decision to automate or retain human labor depends on factors such as economic efficiency, customer satisfaction, company competitiveness, and other internal and external considerations. This research contributes to the existing literature by addressing the specific context of Indonesia and providing insights into the current state and potential future applications of RAISA in the hospitality, travel, and tourism industry. It highlights the scarcity of research in this area and emphasizes the need for further investigation, particularly in areas such as the economic rationale of service automation, the readiness of businesses to adopt RAISA, stakeholder attitudes towards service robots, the impact of RAISA on service quality and company competitiveness, and the ethical considerations associated with its implementation. The findings of this study offer valuable insights for industry practitioners, policymakers, and researchers aiming to understand the benefits, challenges, and implications of integrating RAISA in the Indonesian tourism industry.